Implementation Of Fraud Hexagon On Financial Statement Fraud: Systematic Literature Review - Nataniela, Cita Tasha (International Economic Conference of Business and Accounting, 2024)
This research aims to analyze and compare research results related to the influence of the fraud hexagon on fraudulent State-owned Company reports in Indonesia to provide new insights regarding future research opportunities. The method used for this research is Systematic Literature Review (SLR) and the literature selection technique used is PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses). The data source used is secondary data in the form of research articles from the Google Scholar database with a period of 2020-2023. There were 11 articles that met the inclusion criteria in this study. The results of this research show that there is only 1 type of research method carried out in this article, namely quantitative methods with secondary data collection techniques, namely open State-owned Company financial reports and the factors most researched are financial stability, turnover, and external pressure so that these three factors can be used as control variables in future research. Meanwhile, other factors, namely financial targets, nature of the industry, ineffective monitoring, change of directors, cooperation with the government, quality of external auditors, total accruals on assets, number of CEO’s pictures, and CEO duality can be used as additional variables that can be tested again to see the consistency of a study.